OUTCOMES OF SURGICAL TREATMENT OF DRUG RESISTANT EPILEPSY - Abduvoyitov Bobur Bahodirovich (Research Focus International Scientific Journal, 2025)
Background. Pharmacoresistant epilepsy (PRE) remains one of the most challenging neurological conditions, often unresponsive to pharmacological therapy. Surgical intervention is considered the most effective treatment option for selected patients. Objective. This article summarizes current approaches and outcomes of surgical treatment for PRE, highlighting prognostic factors, surgical techniques, neuropsychological outcomes, and quality of life (QoL) considerations. Methods. A review of contemporary literature was conducted, analyzing prospective and retrospective studies, meta-analyses, and clinical trials evaluating outcomes after anterior temporal lobectomy with amygdalohippocampectomy (ATL+AH), selective amygdalohippocampectomy (SAH), and minimally invasive techniques, including MRI-guided laser interstitial thermal therapy (MgLiTT), stereoelectroencephalography-guided radiofrequency thermocoagulation (SEEG-guided RFTC), and neuromodulation procedures (vagus nerve stimulation, deep brain stimulation, and responsive neurostimulation). Favorable surgical outcomes are strongly associated with concordant neuroimaging and EEG findings, as well as the extent of resection of the epileptogenic zone. ATL+AH remains the gold standard, demonstrating seizure freedom in up to 70–80% of patients, while SAH offers comparable seizure control with improved preservation of neurocognitive functions. Minimally invasive techniques and neuromodulation provide alternative options for patients with multifocal or surgically inaccessible lesions. Neuropsychological assessments indicate that surgery can halt cognitive decline associated with ongoing seizures and improve QoL, although risks of postoperative deficits remain, particularly with left-sided resections. Multiple studies confirm significant postoperative improvement in QoL scores (QOLIE-31), especially in seizure-free patients. Conclusion. Surgical treatment of PRE is superior to long-term pharmacotherapy in carefully selected patients, providing seizure freedom, stabilization of cognitive functions, and improved QoL. Early identification of pharmacoresistance and timely surgical referral are crucial for optimizing long-term outcomes.